Comparative Study of Nutrient Status of Peel and Edible Parts of Cucumber (Cucumis sativus) Grown in Arid Zone - Chaturvedi, Shivani; Kharkwal, H B; Rawat, P S; Kumar, Narendra (Annals of Arid Zone, 2016)
Short Communication